Predicting Audit Qualifications with Financial and Market Variables. - Dopuch, Nicholas; Holthausen, Robert W.; Leftwich, Richard W. (The Accounting Review, 1987)
Abstract ABSTRACT: This paper investigates the extent to which models based on financial and market variables predict auditors' decisions to issue qualified audit reports in situations involving contingencies or uncertainties. A probit model is developed with the dependent variable indicating whether the firm received a qualified opinion, and the independent variables representing publicly available financial and market variables. The estimated model distinguishes between unqualified (clean) opinions and first-time qualifications and between types of qualifications (e.g., going concern, litigation, asset realizing, and multiple qualifications) in the year of the qualification, for both an estimation sample and a holdout sample. The predictive accuracy of the estimated model is evaluated in terms of misclassification costs for alternative costs of type I and type II errors and for specific prior probabilities of qualified and clean opinions.